Sarcoidosis and Common Variable Immunodeficiency: Similarities and Differences - Verbsky, James W.; Routes, John M. (Seminars in Respiratory and Critical Care Medicine, 2014)
Common variable immunodeficiency (CVID) is a primary immunodeficiency that is characterized by hypogammaglobulinemia and poor/absent specific antibody production. Granulomatous and lymphocytic interstitial lung disease (GLILD) is an increasingly recognized complication of CVID, occurring in 10 to 20% of patients. GLILD is characterized by non-necrotizing granuloma, lymphocytic interstitial pneumonitis and follicular bronchiolitis-histological patterns that are typically present in the same biopsy. GLILD is a multisystem disease and is frequently accompanied by diffuse adenopathy, splenomegaly, and extrapulmonary granulomatous disease most commonly in the lymph nodes, spleen, liver, and gastrointestinal tract. The presence of noncaseating granuloma in the lung along with some of the extrapulmonary features of GLILD may lead to an incorrect diagnosis of sarcoidosis. However, GLILD differs from sarcoidosis in several important ways including mode of presentation, extrapulmonary manifestations, radiographic abnormalities on high-resolution computed tomography scan of the chest, and laboratory features (serum immunoglobulins, bronchoalveolar lavage, and histopathology). The misdiagnosis of sarcoidosis in a patient with CVID and GLILD can lead to inappropriate treatment and increase the morbidity and mortality of the disorder.
Keywords: common variable immunodeficiency; sarcoidosis; granulomatous and interstitial lung disease; immunodeficiency